Determining the Effects of Water Sources on Concrete Properties - Wisdom D. Adzraku; Peter P. Yalley; Kennedy Appiadu-Boakye (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
This study investigates the effects of water sources on concrete properties. Water alone as a factor comes with impurities that may interfere with the setting of the cement paste and adversely affect the strength of the concrete. Some solvents in water also cause staining on the surface of the concrete as well as lead to corrosion of the reinforcements embedded in the concrete and thereby render the building structure susceptible to decay or eventual failure. A mix ratio of 1:1.5:3 with 0.5w/c was used in mixing the concrete. Water from the Stream, the hand-dug well, and the borehole were used for the experiments with pipe-borne water serving as the control. Cubes and beams were cast and tested for compression and flexural strengths respectively at 7-day and 28-day curing ages. The chemical and physical properties of the water samples were also tested. The results indicate that the chemical impurities of all the water types were within the limits given in GS 175-1:2009, EN 1008, ASTM C94, and AS 1379. Notwithstanding the fact that the required physical specifications for all the specimens were satisfactory, the specimens mixed with stream water however, were seen to be yellowish and this can be attributed to the quality of the stream water, The water sources had no significant effect on the workability of concrete. Except for specimens obtained from the stream water effects of efflorescence were not observed on hardened concrete specimens obtained from the water sources. Concrete Specimens mixed with water from the hand-dug well had the highest compressive strength. Flexural strengths gained from mixing concrete with the use of water from alternative sources should compete with values obtained when potable water is used. Although these Water samples that were studied did not attain the maximum parameters in terms of specifications for water fit for drinking as well as for mixing concrete, they, with the exception of samples from the stream water, did not show any signs of staining nor efflorescence.